MODEL OF ANALYSIS AND MANAGEMENT OF AGRIBUSINESS INNOVATION SYSTEMS: NEW HORIZONS OR CHAOS? - Paez, Maria Lúcia D'Apice (Science & Technology Journals, 2001)
The aim of this paper is to propose a model to analyze and manage agribusiness innovation systems in those public organizations dedicated to Research & Development (R&D) under the theoretical terms of the New Institutional Economics. This model conceptual base arose from Coase-Williamson-Penrose’s contributions in which is assumed a "bounded determinism" derived from uncertainties of human behavior together with these of the external environments, affecting key variables relationships. The limits of the innovative firm are considered flexible reaching "sustainable fitters," strategically designed to "seek profits" over time but made up of "remediable fitter" efficiencies which are farsighted viewed and organized as a discrete, comparative, economizing governance solution at a given time and place. Additional hypothesis is raised that, independently of the hierarchy of the system under analysis, this logical "process" of sustainable equilibria can be repeated but their "products" are "interrelated" to own contexts. The "dynamic capabilities approach" due to Teece-Pisano-Shuen gave operational content to the systemic model developed and a quantitative treatment based on the theory of chaos is suggested to be utilized near future.